Efektivitas Prenatal Yoga Terhadap Nyeri Punggung Pada Ibu Hamil Trimester III - Purwandari, Atik; Lontaan, Anita; Daud, Sonatalia (POLTEKKES KEMENKES MANADO, 2024)
Background: During pregnancy, there are usually many complaints or discomforts that usually occur. One of them is back pain that occurs in pregnant women in the third trimester. One of the efforts to overcome back pain complaints is prenatal yoga. Prenatal yoga can flex the muscles around the spine and flex the body. Objective: This study was to determine the effectiveness of prenatal yoga on back pain in pregnant women in the third trimester. Methods: This study uses the design of One Group Pre Test—Posttest using an experimental method. The sample in this study is pregnant women in the third trimester who experience back pain with a sample size of 30 respondents. This sampling was done using the Total Sampling method and the measuring tool used was the Visual Analog Scale (VAS). Results: The study showed that before performing Prenatal Yoga in the trimester, most of the respondents experienced moderate pain as many as 21 respondents (73.3%) and 9 respondents (26.7%) had mild pain. Then after doing Prenatal Yoga, there was a decrease in pain which became mild pain as many as 21 respondents (70%), 8 respondents (26.7%) who became no pain and 1 respondent (3.3%) remained moderately painful. The statistical test used in this study was the Wilcoxon test and obtained a significance p value = 0.00 (:0.05) meaning that there was a significant difference in back pain before and after prenatal yoga. Based on the results of this study, it is hoped that prenatal yoga techniques can be applied, especially to overcome back pain complaints in pregnant women in the third trimester. Conclusion: Prenatal Yoga can be applied in various health services as one of the non-pharmacological methods and complementary therapies in overcoming complaints that are often felt by pregnant women such as back pain.